2018
DOI: 10.1103/physrevmaterials.2.075601
|View full text |Cite
|
Sign up to set email alerts
|

Searching for crystal-ice domains in amorphous ices

Abstract: We employ classical molecular dynamics simulations to investigate the molecular-level structure of water during the isothermal compression of hexagonal ice (Ih) and low-density amorphous (LDA) ice at low temperatures. In both cases, the system transforms to high-density amorphous ice (HDA) via a first-order-like phase transition. We employ a sensitive local order metric (LOM) [Martelli et. al., Phys. Rev. B, 97, 064105 (2018)], that can discriminate among different crystalline and non crystalline ice structur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 51 publications
2
50
0
Order By: Relevance
“…They described uHDA obtained from PIA of ice I at low temperatures as a derailed state along the polymorphic transition path from crystalline ice I to crystalline ice IV. Similarly, Martelli et al (27) demonstrate in MD simulations that, even though HDA is indeed amorphous (lacking “polydispersed icelike structures”), there exist some small domains structurally reminiscent of ice IV. The bump in the uHDA line is reproducible and implies that near ∼0.5 GPa T x (uHDA) appears to approach T x (eHDA).…”
Section: Resultsmentioning
confidence: 85%
“…They described uHDA obtained from PIA of ice I at low temperatures as a derailed state along the polymorphic transition path from crystalline ice I to crystalline ice IV. Similarly, Martelli et al (27) demonstrate in MD simulations that, even though HDA is indeed amorphous (lacking “polydispersed icelike structures”), there exist some small domains structurally reminiscent of ice IV. The bump in the uHDA line is reproducible and implies that near ∼0.5 GPa T x (uHDA) appears to approach T x (eHDA).…”
Section: Resultsmentioning
confidence: 85%
“…That is, LDA-I derived from uHDA crystalizes into hexagonal ice, whereas LDA-II derived from eHDA crystallizes to stacking disordered ice (or also commonly denoted cubic ice) [49][50][51][52], and they concluded that uHDA contains crystalline hexagonal remnants [55]. Recent MD simulations [56] of both uHDA and eHDA at high pressures showed a 'lack of polydisperse ice-like structures', but a weak indication that uHDA contains a 'nonnegligible number of Ih-like molecules' at elevated pressures of 1.4 GPa, clusters composed of 5-10 molecules [56]. We do not find direct evidence for uHDA containing crystalline hexagonal ice, because e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Also, here the (missing) doping-induced enhancement of the H-atom dynamics clearly differs from the findings for crystalline ices, such as ice I, ice V, and ice XII. Let us also draw attention to recent classical molecular dynamics simulations, which demonstrate that polydispersed ice domains are lacking in both LDA and eHDA [58].…”
Section: Discussionmentioning
confidence: 99%